Homolog-scanning mutagenesis reveals poliovirus receptor residues important for virus binding and replication. - Morrison, M E (1994)
Poliovirus initiates infection of primate cells by binding to the poliovirus receptor, Pvr. Mouse cells do not bind poliovirus but express a Pvr homolog, Mph, that does not function as a poliovirus receptor. Previous work has shown that the first immunoglobulin-like domain of the Pvr protein contains the virus binding site. To further identify sequences of Pvr important for its interaction with poliovirus, stable cell lines expressing mutated Pvr molecules were examined for their abilities to bind virus and support virus replication. Substitution of the amino-terminal domain of Mph with that of Pvr yields a molecule that can function as a poliovirus receptor. Cells expressing this chimeric receptor have normal binding affinity for poliovirus, yet the kinetics of virus replication are delayed. Results of virus alteration assays indicate that this chimeric receptor is defective in converting native virus to 135S altered particles. This defect is not observed with cells expressing receptor recombinants that include Pvr domains 1 and 2. Because altered particles are believed to be an intermediate in poliovirus entry, these findings suggest that Pvr domains 2 and 3 participate in early stages of infection. Additional mutants were made by substituting variant Mph residues for the corresponding residues in Pvr. The results were interpreted by using a model of Pvr predicted from the known structures of other immunoglobulin-like V-type domains. Analysis of stable cell lines expressing the mutant proteins revealed that virus binding is influenced by mutations in the predicted C'-C" loop, the C" beta-strand, the C"-D loop, and the D-E loop. Mutations in homologous regions of the immunoglobulin-like CD4 molecule alter its interaction with gp120 of human immunodeficiency virus type 1. Cells expressing Pvr mutations on the predicted C" edge do not develop cytopathic effect during poliovirus infection, suggesting that poliovirus-induced cytopathic effect may be induced by the virus-receptor interaction.